Game theory : an introduction - Barron, E. N. (Emmanual N.), 1949- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
An exciting new edition of the popular introduction to game theory and its applications The thoroughly expanded Second Edition presents a unique, hands-on approach to game theory. While most books on the subject are too abstract or too basic for mathematicians, Game Theory: An Introduction, Second Edition offers a blend of theory and applications, allowing readers to use theory and software to create and analyze real-world decision-making models. With a rigorous, yet accessible, treatment of mathematics, the book focuses on results that can be used to.
1. Matrix two-person games -- 2. Solution methods for matrix games -- 3. Two-person nonzero sum games -- 4. Games in extensive form : sequential decision making -- 5. N-person nonzero sum games and games with a continuum of strategies -- 6. Cooperative games -- 7. Evolutionary stable strategies and population games.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Game theory; Game theory; MATHEMATICS -- Game Theory; Game theory; Game theory; Electronic books